Cloudy - Pereira, Joshua Ashley (Nanyang Technological University, 2023)
Cloudy is a 2D animated film produced over the span of 3 semesters. Set in a fictionalized Singapore, the film follows Elliot struggling to confide in his mother. However, his world takes an unexpected turn when he encounters a delightful little cloud creature. Ironically, Elliot must now help the creature reunite with its mother before it dissipates entirely!